GAMBARAN KOMUNIKASI PEMIMPIN SEBAGAI BAGIAN DARI KOMUNIKASI ORGANISASI - Christine Natalia; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2019)
Organizational communication has a substantial function to ensure good coordination forachieving organizational effectiveness. Leaders’ communication is an important aspect oforganizational communication, since the way leaders convey their messages would createframing and meaning for their employees about their jobs, their relations with other parts of theorganization, and the working climate. The meaning that employees perceive would have impacton their motivation and involvement to the job and the organization. When the formal system oforganizational communication has not been established yet, employees tend to rely oninformation from their direct leaders. This study aims to explore the description of leaders’communication as a part of organizational communication on PT AV, which has just developedthe formal working system with the limited number of employees. Six leaders from differentmanagerial levels participated to be interviewed in this study which is using a qualitativeapproach. Data was analyzed using theoretical framework of leaders’ communication fromJohansson, Miller and Hamrin (2014), includes initiating structure, facilitating work, relationaldynamic, and representing unit. The results showed that participants did not intensivelycommunicate with their staff regarding the structure of the staff tasks. Participants more relied onSOP and annual meeting. While SOP and job description was not well established yet, theparticipants’ lack of communication on structuring the staff tasks would potentially create lack ofroles and job clarity for staff. Other interesting result was that participants developed their staffsby giving challenging tasks. However, they did not explicitly say to their staff about the intendedmeaning and impacts of giving the tasks. Participants also did not know how their staffsperceived about the tasks. Because there was no open communication on the reason of givingchallenging tasks, it was potentially perceived by staff as additional burden for them. The findingsindicated leaders’ communication was not supported the formal organizational communicationsystem which was not optimally established yet in the organization. This would potentially createunclear and ambigu information received by staff.